Others’ opinions count, but not all of them: anchoring to ingroup versus outgroup members’ behavior in charitable giving - Dorina Hysenbelli; Enrico Rubaltelli; Rino Rumiati (Judgment and Decision Making, 2013)
Because of the large amount of information and the difficulty in selecting an appropriate recipient in the context of charitable giving, people tend to make extensive use of heuristics, which sometimes leads them to wrong decisions. In the present work, we focused on exploring how individuals are influenced by anchoring heuristics and how group membership interacts with this heuristic. In Experiment 1, two different groups of participants were informed about low versus high average donations of other people, and a third control group did not receive any information about the others’ donations. The results showed that participants were willing to donate significantly more in the high-anchor condition compared to the low-anchor condition, as well as about the same amount of money in the low-anchor condition and no-anchor condition. Experiment 2 and 3 showed that high anchors are more effective when the information about others’ donations reflects members of the ingroup rather than the outgroup. Other variables related to these results are further discussed.